Characterization of alkali bonded expanded perlite. (10th December 2018) - Papa, Elettra; Medri, Valentina; Natali Murri, Annalisa; Laghi, Luca; De Aloysio, Giulia; Bandini, Simone; Landi, Elena
Graphical abstract: Highlights: Fine expanded perlite and potassium di-silicate were used as raw material. Partial geopolymerization was promoted. Lightweight alkali bonded material was produced. Compressive strength is1.6 MPa with a density of 467 kg·m −3 . Thermal conductivity is 0.084 W·m −1 K −1 at 25 °C and 0.121 W·m −1 K −1 at 550 °C. Abstract: The thermal and mechanical properties of a lightweight alkali bonded material were investigated in correlation with the microstructure and porosity. The material was produced using fine granules of expanded perlite as raw powder and potassium di-silicate aqueous solution as alkaline activator, instead of the commonly used sodium silicate, to improve thermal performances. After consolidation, the material was subjected to microstructural analyses, as well as to thermo-physical and mechanical tests. Density was 467 ± 40 kg·m −3, the total porosity 80 vol%, the average pore size 0.2 µm and compressive strength was 1.5 ± 0.5 MPa. It was observed that, besides the action of potassium di-silicate as an alkali binder, expanded perlite granules reacted on the surface forming geopolymer nano-precipitates. Laser Flash Method was employed to evaluate the whole thermal behavior within the temperature range 25–550 °C: thermal conductivity was 0.084 m −1 K −1 at 25 °C and 0.121 W·m −1 K −1 at 550 °C. At high temperature, the thermal conductivity resulted similar or even lower when compared with commercial perlite – sodium silicate materials with lower densities in the range 180–260 kg/m 3 . Results show that lightweight alkali bonded expanded perlite materials can be produced with improved thermal properties by exploiting potassium silicate and overcoming the poor temperature resistance of organic binders.